Elemental Analysis of Leaves and Stem Barks Powder of Woodfordia fruticosa - Beck, Neeli Rose (Challenges and Advances in Pharmaceutical Research Vol. 6, 2022)
This chapter aims to investigate essential and trace elements of leaves and stem barks of Woodfordia fruticosa. The phytoconstituents of herbal medicinal plants and the number of trace elements play an important role in the body as curative and preventive agents for combating diseases, nutritive and catalytic disorders. Even at low concentration, the toxic effects of metals are damaging to the human body and all living organisms. It is a necessary step in identifying components and their concentrations in herbal and food products. The current study gives information on the availability of various critical minerals and phytoconstituents that can be used to provide dietary elements and may also aid in the development of new medication formulations.